Insulin-Sensitizing Therapy Attenuates Type 2 Diabetes–Mediated Mammary Tumor Progression - Fierz, Yvonne (American Diabetes Association, 2010)
OBJECTIVE: Type 2 diabetes increases breast cancer risk and mortality, and hyperinsulinemia has been identified as a major factor linking these two diseases. Thus, we hypothesized that pharmacological reduction of elevated insulin levels would attenuate type 2 diabetes–mediated mammary tumor progression. RESEARCH DESIGN AND METHODS: We studied mammary tumor development in MKR(+/+) mice, a nonobese, hyperinsulinemic mouse model of type 2 diabetes. MKR(+/+) mice were either crossed with mice expressing the polyoma virus middle T oncogene specifically in the mammary gland or inoculated orthotopically with the mouse mammary tumor cell lines Met-1 and MCNeuA. MKR(+/+) or control mice harboring tumors were treated with CL-316243, a specific β(3)-adrenergic receptor agonist, which sensitizes insulin action but has no direct effect on the mouse mammary epithelium or Met-1 and MCNeuA cells. RESULTS: CL-316243 treatment significantly reduced the elevated insulin levels in MKR(+/+) mice and, as a consequence, attenuated mammary tumor progression in the three tumor models tested. This effect was accompanied by reductions in phosphorylation of insulin and IGF-I receptors in transformed mammary tissue. CONCLUSIONS: Insulin-sensitizing treatment is sufficient to abrogate type 2 diabetes–mediated mammary tumor progression. Therefore, early administration of insulin-sensitizing therapy may reduce breast cancer risk and mortality in patients with type 2 diabetes.